Directing game animation : building a vision and a team with intent - Jungbluth, Mike (Boca Raton, FL : CRC Pres, 2024)
"Directing Game Animation: Building a Vision and a Team with Intent breaks down the process on how to create an intentional animation vision, that can be both unique and flexible. From defining the high-level experience, to breaking down tech needs, projecting a team size and empowering everyone to work together, this book will help to wrap your arms around a project's animation needs"--
Includes bibliographical references and index.
Keywords: Computer animation; Video games -- Design; Video games industry -- Management; Teams in the workplace